Genesis 5:24 in Karaite Exegesis: "Sefer maamar Mordekhai" - Muchowski, Piotr (The Biblical Annals, 2025)
This article deals with a little-known commentary on the Pentateuch (more precisely, a supercommentary on Aaron ben Joseph’s Sefer ha-mivḥar) titled Sefer maamar Mordekhai (Book of Mordecai’s Speech). Its author is the Polish-Lithuanian Karaite Mordecai ben Nisan of Kukizov (died around the year 1709), one of the founders of the Karaite community in Kukizów near Lwów, the ancestral seat of the Polish king John III Sobieski. This commentary was based on an earlier commentary on Sefer ha-shemenha-tov by Aaron ben Judah, also a Polish-Lithuanian Karaite. Mordecai ben Nisan quotes the text of Sefer ha-shemen ha-tov and adds his own commentary to it. Its importance as an authoritative textbook of Karaite exegesis is evidenced by the fact that it was formally approved for use by leading Karaite scholars of the Polish-Lithuanian communities (between the years 1706 and 1709). Undoubtedly, this commentary should be recognised as the greatest creative achievement of the theological and exegetical thought of the Polish-Lithuanian Karaites, produced during the period of the peak intellectual flourishing of this community (which took place in the 17th-18th centuries). In this article, I present an English edition of the text of this commentary on Genesis 5:24. The edition is based on manuscript C 104, Maamar Mordekhai (manuscript in the collection of the Institute of Oriental Manuscripts, St. Petersburg, 1753). The manuscript contains a commentary on the books of Genesis and Exodus, i.e. up to the parasha Elle pekude (Exodus 38:21–40:38). Another part, containing commentaries on the books of Leviticus, Numbers, and Deuteronomy, was recorded in manuscript C102. The copyist of both volumes was Mordecai ben Samuel of Halicz. He completed the transcription of the text of the commentary (a total of about 1,000 pages) in the month of Ziv, i.e. Iyyar, of the year 1754, see C102, folio 242 verso (the first volume, manuscript C104, was completed in 1753, see C104, folio 3 recto). In the article, I also mention several minor exegetical works of the Polish-Lithuanian Karaites related to Sefer maamar Mordekhai.